Rapid and specific detection of Asian- and African-lineage Zika viruses - Chotiwan, Nunya; Jänisch, Thomas (Science translational medicine, 2017)
LAMP shines light on Zika virus Rapid and simple assays to detect infectious agents are key to tracking emerging epidemics. Chotiwan et al. describe a loop-mediated amplification (LAMP) assay that detects Zika virus RNA in human biofluids such as serum and semen as well as in mosquitoes, the insect vector that transmits the disease. This approach successfully distinguished the Asian-lineage Zika virus, associated with the current outbreak in the Americas, from the African-lineage Zika virus. This LAMP assay should enable tracking of the Asian-lineage strain as it moves into new geographical locations. A key advantage of this approach is detection without the need for RNA purification or copying RNA into DNA.Understanding the dynamics of Zika virus transmission and formulating rational strategies for its control require precise diagnostic tools that are also appropriate for resource-poor environments. We have developed a rapid and sensitive loop-mediated isothermal amplification (LAMP) assay that distinguishes Zika viruses of Asian and African lineages. The assay does not detect chikungunya virus or flaviviruses such as dengue, yellow fever, or West Nile viruses. The assay conditions allowed direct detection of Zika virus RNA in cultured infected cells; in mosquitoes; in virus-spiked samples of human blood, plasma, saliva, urine, and semen; and in infected patient serum, plasma, and semen samples without the need for RNA isolation or reverse transcription. The assay offers rapid, specific, sensitive, and inexpensive detection of the Asian-lineage Zika virus strain that is currently circulating in the Western hemisphere, and can also detect the African-lineage Zika virus strain using separate, specific primers.A rapid, specific, sensitive, and inexpensive method has been developed that detects RNA from a Zika virus strain associated with the current outbreak.A rapid, specific, sensitive, and inexpensive method has been developed that detects RNA from a Zika virus strain associated with the current outbreak.